The impact of COVID‐19 on adolescent wellness in Chicago. (10th March 2022) - Ezeoke, Ogochukwu M.; Kanaley, Madeleine K.; Brown, Dannielle A.; Negris, Olivia R.; Das, Rajeshree; Lombard, Lisa S.; Gupta, Ruchi S.
Abstract: Purpose: This study aimed to understand the impact of the initial COVID‐19 pandemic remote schooling period on self‐reported wellness among adolescents in Chicago. Methods: Students ( n = 55) completed a 22‐item wellness questionnaire before (February 2020) and shortly after the onset of the COVID‐19 outbreak (April 2020). Precomparisons/postcomparisons (overall and by survey item) were evaluated using two‐sided paired t‐tests with an alpha level of 0.05. Descriptive statistics were used to evaluate mean scores overall by demographic variables. Results: Significant differences were found in the following areas: Balance (Pre: 7.3, During: 6.4, p = 0.02), Education (Pre: 8.4, During 7.7, p = 0.03) and Friends (Pre:8.0, During: 6.3, p = 0.001). Overall wellness scores varied by demographic variables, though not significantly. Conclusions: Results suggest the onset of the pandemic impacted students' ability to effectively learn, as well as to maintain balance in their lives and social relationships. Comprehensive support is needed in these areas to promote adolescent wellness.